ADULT–CHILD POWER RELATIONS IN ADDRESS TERMS IN ALICE’S ADVENTURES IN WONDERLAND - Diki Rijki; Eva Utami Durahman; Juwintan Juwintan (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2026)
This study aims to analyze how the use of address terms represents and constructs power relations and social status in the children's storybook Alice's Adventures in Wonderland. Although previous studies have extensively discussed address terms in films, social communities, and digital interactions, most of them focus primarily on politeness and general social factors. This study argues that, in children's literary texts, address terms function not as neutral labels, but as ideological linguistic tools that normalize authority based on age and institutional hierarchy. This research employs a qualitative descriptive method with a sociolinguistic approach. The data consists of address terms found in dialogues between characters in the storybook, collected through reading and note-taking techniques. The data were analyzed by identifying the speaker, the addressee, the social hierarchy, the frequency of occurrence, and the type of social relationship represented, drawing on sociolinguistic theories of address terms, power relations, and age-based authority. The findings reveal that address terms such as your majesty, my dear, child, sir, and miss play an important role in shaping hierarchical relationships between adult and child characters. Address terms like your majesty and child explicitly reinforce institutional and age-based dominance, while my dear functions as an affectionate form that subtly maintains power imbalances. Meanwhile, the use of sir and miss reflects how child characters negotiate authority through politeness and formal recognition. These findings demonstrate that address terms in children's literature actively construct representations of power and social hierarchy rather than merely serving as markers of politeness.